LEGAL AND ETHICAL DIMENSIONS OF XENOTRANSPLANTATION: BIOTECHNOLOGY CROSSING SPECIES BARRIERS - Mr.Souradipta Bandyopadhyay,; Purbita Das,; Upasana Bishnu, (The Bioscan, 2025)
Xenotransplantation, the transplantation of cells, tissues, or organs from one species to another, represents a groundbreaking advancement in biotechnology. However, its potential to address the organ donor shortage is counterbalanced by a host of legal and ethical challenges. A major issue emerges from animals’ being kept under conditions that fail to meet the needs dictated by the animals’ biological and psychological natures. Xenotransplantation animals will be kept under deprived laboratory conditions that similarly fail to meet the animals’ natures. This is a significant concern for society in general. There are also issues of “bad ethics” arising from scientists’ disavowal of ethical concerns in science. This in turn, coupled with societal ignorance of science, creates a climate for proliferation of religious and other non-rational concerns, such as the claim that xenotransplantation violates God’s will. These spurious concerns can only be ameliorated when public understanding of science improves, and scientific understanding of ethics increases. This article explores the interplay between legal frameworks, ethical dilemmas, and scientific progress in xenotransplantation, providing an interdisciplinary perspective on its feasibility and societal implications.